Evaluation of the isokinetic strength of the internal and external rotator, flexor, and extensor muscles of the shoulders in different groups of aquatic activity practitioners - Carneiro, Neice Bahia (Universidade Federal do Amazonas, 2024)
Muscular strength is a determining biomechanical feature of performance in a hydrodynamic environment and its assessment is a common procedure within a training program. This academic dissertation was divided into two articles, which had the following aims: (i) to analyze the effects of front crawl technique used by different groups of aquatic activity practitioners on the isokinetic shoulder joint strength of the internal and external rotator, flexor, and extensor muscles; (ii) to analyze the effect of two angular velocities on the network structures of shoulder isokinetic strength and aquatic activities. Twenty-seven practitioners of competitive swimming (n = 7), open water (n = 7), triathlon (n = 7) and water polo (n = 6) participated in each study. In both articles, the evaluation was carried out using a Biodex System 4.0 isokinetic dynamometer (Biodex Medical Systems, Shirley, NY, USA) with maximum concentric actions in the movements of internal and external rotation, flexion and extension of the shoulders at angular speeds of 60 and 180°/s (three and 20 repetitions, respectively). In the first study, the variables peak torque (N·m), total work (J), coefficient of variation (%), ER/IR ratio and FL/EX ratio (%) and fatigue index (%) were analyzed. In the second, the isokinetic variables (peak torque (N·m) and total work (J)) of the preferred and non-preferred side and aquatic activities (swimming, open water, triathlon and water polo) were used. For the first aim (study 1), the equivalent non-parametric Kruskal-Wallis test was used. The post-hoc test verified differences (p < 0.05) between groups through paired comparisons between competitive swimming vs. open water vs. triathlon and water polo. For the second aim (study 2), the Network Analysis Machine Learning technique was used to verify the multiple simultaneous relationships between isokinetic strength variables and aquatic activities, using three centrality measures in z scores: expected influence, closeness centrality, and strength centrality. The first study showed that, open water practitioners showed lower values of isokinetic strength than water polo for right shoulder internal rotation (total work at 60°/s; p = 0.033, ES = -0.251, and peak torque at 180°/s; p = 0.036, ES = -0.250) and left shoulder flexion (peak torque p = 0.041, ES = -0.248 and total work; p = 0.047, ES = -0.246), both at 60°/s. The front crawl technique used by different groups of aquatic activity practitioners seemed to influence isokinetic strength response on dry land. By learning that these variables might affect performance, coaches of these aquatic activities can identify training strategies to prevent injuries. The second study showed that, by changing the angular velocity, the most prominent variables in the network structures also change concerning the centrality parameters. The total external rotation work of the non-preferred side took a central position at the angular velocity of 60°/s. The variable “aquatic activities” showed a peripheral positioning at both angular velocities. If the angular velocity of 180°/s is considered the closest to the specific features of the aquatic activities represented here, the total work of internal rotation (1.000) and peak torque of extension (0.959), both on the preferred side, showed great influence on performance of these aquatic activities.